Cardiovascular and metabolic outcomes associated with insulin use in type 2 diabetes: evidence from insulin users in the UK primary care - Anyanwagu, Uchenna Chidi (2017)
In clinical use, insulin improves glycaemic control at the cost, typically, of weight gain and more hypoglycaemia – both being risk factors for cardiovascular (CV) disease mortality. The issue of the effect of exogenous insulin on CV disease meanwhile has been debated for a long time. Data on the CV outcomes associated with insulin-treated diabetes in both randomised trials and observational studies have largely been inconsistent. Thus, a balance of the positives and the negatives of insulin therapy needs to be taken into account when prescribing insulin in routine clinical practice, particularly in the context of the progressive nature of diabetes, its requirement for combination glucose-lowering therapy and the availability of novel glucose lowering agents. So, in a cohort of only insulin-users in ‘real-world’ condition, this thesis aims to explore the association between insulin use and CV and metabolic outcomes.